Penerapan Strategi Dynamic Problem Solving untuk Menumbuhkan Keterampilan Proses Sains Mahasisw - Abd. Haris; Muris Muris; Herman Herman (Universitas Negeri Makassar, 2016)
The study aims to know the description of science process skill for basic electronics subject at physics teacher candidate after implemented dynamic problem solving strategies (DPSS), as a novel alternative, to improve teaching and learning process of Physics. This research is included as a pre-experimental with using One Group Posttest Design. The research subject was 23 students of Physics Education Study Program Semester IV for academic year 2015/2016 who take lecturing subject of Basic Electronics. It is concluded that science process skill as follows: 1) students maximum score was 85; 2) minimum score was 80; and 3) the average score was 87,5. In general, the mastery of physics concept and mathematical ability of students especially in basic electronics subject were in good category.